Food systems under shock: the evolution of food security status of Karantina residents after the Beirut explosion - Makoukji, Mariana; Amhez, Nour El Houda; Yehya, Abed Al Kareem; Ghattas, Hala; Abunnasr, Yaser; Zurayk, Rami (Frontiers in Sustainable Food Systems, 2024)
Robust food systems are crucial for ensuring access to affordable and nutritious food, particularly in times of crisis. Economic instability, currency devaluation, and political turmoil can disrupt food systems, leading to higher food prices, compromised nutrition, and increased vulnerability. Lebanon is a stark example of this, where a catastrophic explosion in Beirut’s Port in 2020 worsened an existing economic and humanitarian crisis. The depreciation of the Lebanese currency led to soaring food prices, impacting people’s ability to buy food, and pushing many into poverty, illustrating the significant impact of the state food systems during crises (FAO, 2021). In times of crisis, a simplified food system, relying on emergency food aid supplies, replaces conventional food system, as food aid and cash transfers become the primary source upon which the affected population depends to ensure their food security and meet their essential needs. In this article we report on research conducted between 2020 and 2022 focusing on the impacts of the Beirut explosion on food security status of the permanent residents the Karantina neighborhood—the closest residential area to the Beirut port. We surveyed 100 households chosen at random, examining shifts in food security and nutrition at three intervals: 6 months prior to the explosion, 6 months following it, and 2 years after the event. The findings revealed a sharp decline in food security and diet quality among residents in the two-year period following the explosion. The proportion of food-secure households fell from 71% to 2%, while those with acceptable food consumption decreased from 96% to 30%. Additionally, income and debt situations worsened significantly. Almost 95% of residents resorted to crisis coping strategies, such as using savings, borrowing money for food, selling furniture, withdrawing children from school, and reducing education and health expenses, rendering them highly vulnerable. Food and cash assistance were provided to all households for 6 months to one-year post-explosion, resulting in improved food security and consumption after 6 months. However, these gains diminished 2 years later, once the assistance ended, revealing a lack of resilience in the food system. In conclusion, soon after the assistance stopped, the prolonged deterioration of Lebanon’s economic situation, compounded by multiple crises, pushed these households further into poverty, exacerbating food insecurity. This research underscores the critical importance of sustained support and comprehensive economic reforms to rebuild food systems and promote nutrition resilience in crisis-affected regions.